Legal Review of Song Copyright Protection for the Realization of Legal Certainty - Ramdani, Gilang; Pratama, Mochammad Andre; Maulana N.T, Avicenna; Sutrisno , Endang; Daulay , Annisa Angraini (PT FORMOSA CENDEKIA GLOBAL, 2025)
Digital technology has made it easier to access music and digital platforms. Still, this development has made it easier to infringe on song copyright, preventing the protection of Song Copyright from running optimally. This research examines the relationship between legal provisions on Copyright and the legal protection afforded to song creation under Law No. 28 of 2014 respecting Copyright. This study employs normative juridical research methods utilizing legal and comparative approaches. The results of the study found that although Copyright protection has regulated various rights of copyright owners to protect their rights, in practice Copyright infringement still occurs frequently, this is because the current Law still does not provide a clear legal framework for parties who provide space so that it allows Copyright infringement to occur, such as the digital platform Youtube, and lacks strict enforcement of the law against copyright infringers, therefore to achieve legal certainty in providing copyright protection to copyright owners. The legislation must establish a definitive legal framework delineating the responsibilities of digital platforms concerning the content hosted on their sites, alongside the necessity for organized oversight by the Collective Management Institution to serve the public utilizing the song for commercial purposes in relation to their obligation to remit royalties. Furthermore, rigorous enforcement of the law against copyright infringers is essential to achieve legal certainty in the safeguarding of copyright.